2016
DOI: 10.1002/ep.12467
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of low density polyethylene

Abstract: Low‐density polyethylene (LDPE) is potential source of environmental pollution. In this study, biodegradation of LDPE was achieved by employing fungus and actinobacteria isolated from waste dumping site. Among all the isolates, two potential strains were obtained through enrichment technique. Based on 18S rRNA and 16S rRNA analyses the isolated strains were identified as Aspergillus nomius and Streptomyces sp., respectively. The biodegradation of LDPE was determined by evaluating weight loss and morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(33 citation statements)
references
References 42 publications
(50 reference statements)
0
26
0
1
Order By: Relevance
“…Saccharothrix wayandensis, etc.) have shown either weight reduction or partial degradation of PE films (Sivan et al, 2006;Abraham et al, 2017;Huang et al, 2019;Soulenthone et al, 2020). Among the fungal species, members of Aspergillus (Muhonja et al, 2018); Fusarium (Sivan, 2011); Penicillium, Zalerion (Raddadi and Fava, 2019); Chaetomium and Pullularia (Sudhakar et al, 2008) are well known for biodegradation of LDPEs and HDPEs.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharothrix wayandensis, etc.) have shown either weight reduction or partial degradation of PE films (Sivan et al, 2006;Abraham et al, 2017;Huang et al, 2019;Soulenthone et al, 2020). Among the fungal species, members of Aspergillus (Muhonja et al, 2018); Fusarium (Sivan, 2011); Penicillium, Zalerion (Raddadi and Fava, 2019); Chaetomium and Pullularia (Sudhakar et al, 2008) are well known for biodegradation of LDPEs and HDPEs.…”
Section: Introductionmentioning
confidence: 99%
“…The current trend is the utilization of several potential microbes especially bacteria for decontaminating the cultivated lands from chemically synthesized pesticides. Several studies have reported the elimination of such toxic chemicals using microbial degradation as well as synthetic polymers in environment‐friendly ways [20–22]. Considering the alarming consequence of carbofuran toxicity, an LC 50 of carbofuran (99%) was measured against A. salina , which was 9.103558 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“… Aspergillus niger LDPE (20µm) 30 days 5.8 [ 44 ] 6. Rhodococcus ruber LDPE (0.2mm) 60 days 7.5 [ 45 ] 7. Pseudomonas putida LDPE (20µm) 120 days 9 [ 30 ] 8.…”
Section: Introductionmentioning
confidence: 99%